Running in the heat: Performance consequences and strategies to prepare for hot-weather racing - Ely, B. R.; Ely, M. R. (Strength and Conditioning Journal, 2020)
Competitive runners seek to control as many performance variables as possible when preparing for peak competition. However, race day weather is out of an athlete's control and can have a profound impact on performance. This review defines hot weather in terms of running performance, details the physiology underlying heat-related performance decrements, and discusses strategies that may mitigate the negative impact of heat on cardiovascular strain and attenuate reductions in heat-related running performance.